Efficiency of laser excitation of PO photofragments of organophosphates - Bobrovnikov, Sergei M. (Atmospheric and oceanic optics)
Results of calculation of the absorption spectrum of phosphorus oxide (PO) corresponding to the A2Σ+ (v′ = 0) − X 2Π (v′′ = 0) transition are presented. The calculation is performed taking into account the perturbation of the v′ = 0 level of the A2Σ+ state by the v′ = 4 level of the b4Σ− state. The efficiency of laser excitation of PO molecules is estimated as a function of the spectral parameters of the radiation. The time dependence of the efficiency of the excitation of PO fragments is calculated for a real atmosphere under two-pulse laser fragmentation of organophosphates for specified spectral linewidths Δλ and center positions λ0.